A Room‐Temperature Postsynthetic Ligand Exchange Strategy to Construct Mesoporous Fe‐Doped CoP Hollow Triangle Plate Arrays for Efficient Electrocatalytic Water Splitting. Issue 14 (23rd February 2018) - Hu, Enlai; Ning, Jiqiang; Zhao, Dian; Xu, Chunyang; Lin, Yingying; Zhong, Yijun; Zhang, Ziyang; Wang, Yongjiang; Hu, Yong
Abstract: Hollow nanostructures with mesoporous shells are attractive for their advantageous structure‐dependent high‐efficiency electrochemical catalytic performances. In this work, a novel nanostructure of Fe‐doped CoP hollow triangle plate arrays (Fe–CoP HTPAs) with unique mesoporous shells is designed and synthesized through a room‐temperature postsynthetic ligand exchange reaction followed by a facile phosphorization treatment. The mild postsynthetic ligand exchange reaction of the presynthesized ZIF‐67 TPAs with K4 [Fe(CN)6 ] in an aqueous solution at room temperature is of critical importance in achieving the final hollow nanostructure, which results in the production of CoFe(II)‐PBA HTPAs that not only determine the formation of the interior voids in the nanostructure, but also provide the doping of Fe atoms to the CoP lattice. As expected, the as‐prepared mesoporous Fe–CoP HTPAs exhibit pronounced activity for water splitting owing to the advantages of abundant active reaction sites, short electron and ion pathways, and favorable hydrogen adsorption free energy (Δ G H* ). For the hydrogen and oxygen evolution reactions with the Fe–CoP HTPAs in alkaline medium, the low overpotentials of 98 and 230 mV are observed, respectively, and the required cell voltage toward overall water splitting is only as low as 1.59 V for the driving current density of 10 mA cm −2 . Abstract : A room‐temperature postsynthetic ligand exchange reaction followed by a facile phosphorization treatment is demonstrated to construct Fe‐doped CoP hollow triangle plate arrays with unique mesoporous shells aiming at achieving an active, stable, and low‐cost electrocatalyst toward overall water splitting.